Behavior of nurses and nurse aides toward influenza vaccine: the impact of the perception of occupational working conditions. Issue 5 (3rd May 2020) - Mignot, Alexandre; Wilhelm, Marie-Claire; Valette, Annick; Gavard-Perret, Marie-Laure; Abord-De-Chatillon, Emmanuel; Epaulard, Olivier
ABSTRACT: Although influenza vaccination of hospital healthcare workers (HCWs) has been associated with a reduction in patient mortality and morbidity, HCW vaccine coverage is low in France. Previous studies identified the role of perceptions of vaccine efficacy and safety as well as practical issues (e.g., limited time). We aimed to determine whether HCW behavior toward influenza vaccine was associated with occupation-related psycho-social issues and perceptions of management. Between February and August 2018, an anonymous online questionnaire explored the perceptions and behavior of nurses and nurse aides regarding the influenza vaccine, as well as the perceived quality of professional management, perceived psychological contract breach, perceived workload, and compassion fatigue using previously validated scales. Among the 791 respondents (mean age 36.9 ± 10 years, female 85.0%; nurses 76.4%), 28.6% had been vaccinated during the current year (i.e., the study year) and 13.0% during the previous year. Among those not vaccinated during the study year, their vaccination intention for the coming year on a 1–5 scale was 1/5 for 68.5% and 5/5 for 15.4%. Positive behavior/intention regarding the influenza vaccine (recent vaccination and/or high future intention) was positively correlated with perceptions of management and negatively correlated with feelings of a psychological contract breach and compassion fatigue. In multivariate analysis, this positive behavior/intention was correlated with management perception independently of the perceptions of vaccination itself. Among nurses and nurse aides, the propensity to be vaccinated appears to depend closely on the perceived working conditions. These factors should be addressed when promoting vaccination among these populations.